Indium-mediated diastereoselective allylation reactions: preparation of alpha-hydroxy and alpha-amino acids - Lee, JG; Choi, KI; Pae, AN; Koh, HY; Kang, YH; Cho, YS (ROYAL SOC CHEMISTRY, 2002)
The hemiacetals of (+)- and (-)-N-glyoxyloylbornane-10,2-sultam and their imines reacted with allyl iodide in the presence of indium in DMF to give the corresponding alpha-hydroxy and alpha-amino camphor sultam derivatives with high diastereoselectivities (86-90% de). This method could be useful for preparation of alpha-hydroxy and alpha-amino acids.